Soil indicators of hydrologic health and resilience in cypress domes of West-Central Florida. (February 2019) - Moore Powell, Katherine; Wynn, Jonathan G.; Rains, Mark C.; Stewart, Mark T.; Emery, Scott
Highlights: Accumulation of organic matter in cypress wetlands retains soil moisture. Extensive soil saturation is needed to preserve wetland resilience. Altered water balances that shift plant communities reinforce wetland degradation. Soil moisture sampling may determine groundwater withdrawal impacts to wetlands. Soil carbon isotopes indicate wetland plant community shifts to drier conditions. Abstract: Groundwater pumping in west-central Florida has caused water table declines that disrupt hydroperiods and negatively impact already threatened, geographically isolated freshwater wetlands in this region. Currently, aboveground biological indicators are used to determine the health status of wetlands impacted by groundwater withdrawals, however some soil properties, such as organic matter content, are partly a function of the duration of saturation and could be used as additional indicators. Therefore, this study evaluated soil organic carbon and related soil properties for comparison with the biological indicators of wetland health status. Soil samples were taken from the top 30 cm of the land surface (i.e., bulk density, soil water content, nitrogen content, and carbon and nitrogen isotopic composition) within pond cypress ( Taxodium ascendens ) domes previously categorized by the local water management district using wetland health classifications of "healthy", "significantly changed", or "severely changed". Mean soil water content ( w ) was significantly higher in "healthy" wetlands as compared to "significantly changed" and "severely changed" sites, and "healthy" sites also tended to have lower bulk density and higher soil carbon and soil nitrogen content. This trend was most pronounced toward the center and lowest elevation of the wetland, presumably where soils remain saturated longest. Stable carbon isotope values (δ 13 C) of soil organic matter showed that "severely changed" sites exhibited more 13 C-enriched values that arise from long term contributions of warm-season (C4 ) grasses, consistent with the observed upland grasses encroaching into the most impacted wetlands. Notably, soil characteristics may be crucial for determining the resilience of wetlands, as one sampled "healthy" site contained comparably less soil organic matter, reducing the water holding capacity and leaving it more vulnerable to water table declines. These results suggest that extensive annual saturation of soils is required to maintain the cypress dome ecological community structure and preserve wetland health and resilience. Frequent monitoring of soil water may prove a convenient proxy for soil water retention properties and ecosystem health of wetlands in similar settings.